Effects of a Mindfulness-based Program on Children’s Social Skills, Problem Behavior, and Emotion Regulation - (:unkn) unknown (My University, 2018)
This quasi-experimental wait-list control study examined the effects of a mindfulness-based program on students in two open-enrollment public charter schools located in a mid-sized urban city. Participants (n=176) were 3rd through 6th grade students. Students were identified as 54% Hispanic/Latino, 39% African American, and 7% other (e.g., White, Asian, American Indian). Three classrooms at each school served as the treatment group, and three classrooms at each school served as the control group, for a total of 12 participating classrooms. Students and teachers reported on students’ social skills, problem behavior, emotion regulation, and mindfulness before and after the program. The mindfulness program was taught twice a week for 10-weeks. Each session lasted approximately 20 minutes and was implemented in all six treatment classrooms by a trained mindfulness instructor. Multivariate analysis of covariance (MANCOVA) and analysis of covariance (ANCOVA) were the primary methods of analyses. After controlling for pre-treatment levels of each variable, gender, and age, results indicated no significant differences in student-reported social skills, problem behavior, or mindfulness between the treatment and control groups. Teachers reported no significant differences between the control and treatment groups’ emotion regulation, empathy, engagement, self-control, externalizing, and internalizing at post-test. However, teachers did report significantly higher cooperation and significantly lower hyperactivity/inattention for children in the treatment group at post-test. Interaction effects of gender by treatment group indicated males in the treatment group appeared to benefit significantly more than females in the treatment group in terms of hyperactivity/inattention. In addition, the effects of problem type were analyzed in an exploratory manner. Implications of this study suggest mindfulness may have particular utility to improve children’s cooperation and reduce hyperactive and inattentive symptoms specifically for males. Although more research is needed, results also indicated that mindfulness may have particular utility as a universal intervention. After the implementation of the mindfulness program, children with externalizing and internalizing problems appeared to have levels of emotion regulation that were not significantly different from their typical peers.
Keywords: Emotion Regulation; Mindfulness; Problem Behavior; Schools; SEL; Social Skills